Impacts of saline water intrusion on the daily lives in the Mekong Delta Viet Nam - Bergqvist , Anna; Eitrem Holmgren, Katrin; Rylander , Pehr (2012)
We conducted a field study in the coastal province of Ben Tre, Viet Nam. Saline intrusion is a reality for people living in this province and one objective of our study was to ask for views and consequences of this phenomenon. The study was conducted by making qualitative interviews with farmers and various authorities in the province during the spring of 2011. Water samples were collected and the total electrical conductivity was measured in order get an understanding of the range of saline levels in the region. The study was done in cooperation with Can Tho University, Viet Nam and the Swedish University of Agricultural Sciences, Sweden.